Pharmacodynamics, pharmacokinetics and safety of revefenacin (TD-4208), a long-acting muscarinic antagonist, in patients with chronic obstructive pulmonary disease (COPD): Results of two randomized, double-blind, phase 2 studies. (February 2018) - Quinn, Dean; Barnes, Christopher N.; Yates, Wayne; Bourdet, David L.; Moran, Edmund J.; Potgieter, Peter; Nicholls, Andrew; Haumann, Brett; Singh, Dave
Abstract: Background: Revefenacin (TD-4208) is a potent, lung-selective, long-acting muscarinic antagonist currently in development as a once-daily nebulized therapy for chronic obstructive pulmonary disease (COPD). We evaluated the pharmacodynamics (bronchodilator activity), pharmacokinetics (PK) and safety of single- and multiple-dose administrations of revefenacin in two clinical trials (Study 0059 and Study 0091) in patients with moderate to severe COPD. Methods: In Study 0059, 32 patients were randomized to receive a single dose of revefenacin (350 or 700 μg), active control ipratropium (500 μg) or placebo inhalation solution administered via standard jet nebulizer in a double-blind, crossover fashion. In Study 0091, 59 patients were randomized to receive once-daily inhalations of revefenacin (22, 44, 88, 175, 350 or 700 μg) or placebo for 7 days in a double-blind, incomplete block, five-way crossover design. The primary efficacy endpoint was change from baseline in peak (0–6 h) forced expiratory volume in 1 s (FEV1 ) in Study 0059, and trough FEV1 after the final dose (Day 7) in Study 0091. In both studies, secondary endpoints included area under the FEV1 -time curve (FEV1 AUC) values from time 12–24 h post dose and FEV1 AUC values from time zero to 24 h post dose. Results: Revefenacin demonstrated a rapid onset and sustained duration of bronchodilator action in both studies. In Study 0059, mean peak FEV1 was significantly higher ( p < 0.001) for revefenacin and ipratropium compared to placebo, with differences of 176.8 mL for 350 μg revefenacin, 162.2 mL for 700 μg revefenacin and 190.6 mL for ipratropium. In Study 0091, mean trough FEV1 on Day 7 was significantly higher ( p < 0.006) for all revefenacin doses compared to placebo, with differences ranging from 53.5 mL (22 μg dose) to 114.2 mL (175 μg dose). The results for the other spirometry endpoints were consistent with the primary endpoint for each study, demonstrating that the bronchodilator effect of revefenacin lasted more than 24 h following nebulized administration. Revefenacin was rapidly absorbed and extensively metabolized, followed by a slow apparent terminal elimination and minimal accumulation with repeated dosing. In both studies, adverse events were generally mild and occurred with similar frequencies in all groups, with no indication of significant systemic anti-muscarinic activity at any dose. Conclusions: Following single or multiple nebulized-dose administration in patients with COPD, revefenacin demonstrates a rapid onset and sustained duration of bronchodilator effect over 24 h following once-daily administration, with a PK profile that is commensurate with low systemic exposure.